Health workforce governance for compassionate and respectful care: a framework for research, policy and practice. Issue 3 (31st March 2022) - Cometto, Giorgio; Assegid, Samuel; Abiyu, Geta; Kifle, Mesfin; Tunçalp, Özge; Syed, Shamsuzzoha; Kleine Bingham, Melissa; Nyoni, Jennifer; Ajuebor, Onyema Kester
Abstract : The progressive realisation of universal health coverage requires that health services are not only available and accessible, but also that they are rendered to the population in an acceptable, compassionate and respectful manner to deliver quality of care. Health workers' competencies play a central role in the provision of compassionate and respectful care (CRC); but health workers' behaviour is also influenced by the policy and governance environment in which they operate. The identification of relevant policy levers to enhance CRC therefore calls for actions that enable health workers to optimise their roles and fulfil their responsibilities. This paper aims at exploring the health workforce policy and management levers to enable CRC. Through an overview of selected country experiences, concrete examples are provided to illustrate the range of available policy options. Relevant interventions may span the individual, organisational, or system-wide level. Some policies are specific to CRC and may include, among others, the inclusion of relevant competencies in preservice and in-service education, supportive supervision and accountability mechanisms. Other relevant actions depend on a broader workforce governance approach, including policies that target health workforce availability, distribution and working conditions, or wider system -level factors, including regulatory and financing aspects. The selection of the appropriate system-wide and CRC-specific interventions should be tailored to the national and operational context in relation to its policy objectives and feasibility and affordability considerations. The identification of performance metrics and the collation and analysis of required data are necessary to monitor effectiveness of the interventions adopted.